2011
DOI: 10.1186/1471-2164-12-416
|View full text |Cite
|
Sign up to set email alerts
|

Tight associations between transcription promoter type and epigenetic variation in histone positioning and modification

Abstract: BackgroundTranscription promoters are fundamental genomic cis-elements controlling gene expression. They can be classified into two types by the degree of imprecision of their transcription start sites: peak promoters, which initiate transcription from a narrow genomic region; and broad promoters, which initiate transcription from a wide-ranging region. Eukaryotic transcription initiation is suggested to be associated with the genomic positions and modifications of nucleosomes. For instance, it has been recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…H3K4 methyltransferases associate with the C-terminal domain S5ph form of RNA polymerase II (25), and this explains why H3K4me3 is preferentially associated with the nucleosomes of the proximal coding region (18,19,21). However, histone exchange frequently occurs in the "hot" nucleosomes found in regulatory regions and at the beginning of the gene body, and Henikoff (53) proposed that methylation of H3K4 is related to histone turnover.…”
Section: Discussionmentioning
confidence: 99%
“…H3K4 methyltransferases associate with the C-terminal domain S5ph form of RNA polymerase II (25), and this explains why H3K4me3 is preferentially associated with the nucleosomes of the proximal coding region (18,19,21). However, histone exchange frequently occurs in the "hot" nucleosomes found in regulatory regions and at the beginning of the gene body, and Henikoff (53) proposed that methylation of H3K4 is related to histone turnover.…”
Section: Discussionmentioning
confidence: 99%
“…28,[46][47][48] Here we discuss the complex core promoter regulation of CR2/CD21, the expression of which is cell type-specific and inducible. We have identified core promoter elements in the CR2/CD21 core promoter including TATA box, GC box, Inr and DPE sequences.…”
Section: Discussionmentioning
confidence: 99%
“…25 Recent studies have attributed the core promoter with a more complex role in regulation of gene expression. [26][27][28][29] The concepts that have emerged are that core promoters are tailored to their biological function and act as the convergence point for long-range and cis-acting regulators of transcription. In the experiments outlined in this report, we assessed the role of the CR2/CD21 core promoter in driving transcription initiation in B cells.…”
Section: Introductionmentioning
confidence: 99%
“…These two promoter classes have also been found in Drosophila melanogaster (Rach et al 2009;Ni et al 2010;Hoskins et al 2011), but there is a difference in the associated motifs between human and Drosophila; the broad-type promoters in Drosophila are more likely to be associated with nonpositionally fixed motifs such as a DNA replication-related element (DRE) (Ni et al 2010). In human and Drosophila, it has been shown that broad-type promoters exhibit more precise nucleosome positioning than sharp-type promoters (Nozaki et al 2011;Rach et al 2011), and human broad-type promoters have been shown to exhibit a 10.5-bp periodic distribution of WW (where W is A or T) motifs at the region corresponding to the position of the +1 nucleosome downstream from the dominant TSS (Forrest et al 2014). As for ribosomal protein (RP) gene promoters, in human and Drosophila, it has been shown that they possess a polypyrimidine initiator motif, where transcription starts with a cytosine nucleotide, and exhibit a sharp-type TSS distribution (Yoshihama et al 2002;Perry 2005;Yamashita et al 2008;Parry et al 2010).…”
mentioning
confidence: 97%